A seed layer induced FeCoNiCuMo high entropy alloy nanocage electrocatalyst and its preparation method and application

The preparation of FeCoNiCuMo high-entropy alloy nanocage electrocatalysts through seed layer induced, solving the problems of low activity and insufficient reaction kinetic matching in the process of CO2 and NO3-electrocatalyzed urea preparation, and achieving efficient and highly selective urea synthesis.

CN119187590BActive Publication Date: 2025-03-14QUZHOU RES INST OF ZHEJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411686553.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-14
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing catalysts have low activity in the process of electrocatalyzing urea preparation of CO2 and NO3-, and the kinetic matching of CO2 and NO3-parallel reactions is insufficient, resulting in limited urea yield.

Method used

The preparation method of FeCoNiCuMo high-entropy alloy nanocage electrocatalyst is used to induce the seed layer. The FeCoNi nanocage is used as a template and treated with pH adjustment and reducing agent to form a high-entropy alloy catalyst with a specific morphology and structure, adjust the electronic and geometric properties of the catalyst and improve the catalytic performance.

Benefits of technology

The matching of CO2 and NO3-reaction kinetics is significantly improved, the selectivity of catalysts for C-N bond formation is enhanced, the yield and Faraday efficiency of urea are improved, and the catalyst still has good stability under long-term work.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119187590B_ABST
    Figure CN119187590B_ABST
Patent Text Reader

Abstract

The present invention discloses a seed layer induced FeCoNiCuMo high entropy alloy nano cage electrocatalyst and its preparation method and application. The preparation comprises the following steps: preparing FeCoNi nano cage catalyst as seed layer by mixed reaction of iron, cobalt and nickel precursors; adding copper salt and molybdate to seed layer solution for ultrasonic mixing; adding pH regulator and reducing agent for ultrasonic treatment; placing the mixed solution in liquid nitrogen for cooling for preliminary nucleation; standing for nucleation after natural thawing; washing and freeze drying to obtain the high entropy alloy nano cage electrocatalyst. The catalyst is used for CO2 and NO3 ‑ Electrocatalytic preparation of urea can effectively adjust CO2 and NO3 ‑ The reaction kinetics are well matched, and the C-N coupling synthesis of urea has extremely high Faradaic efficiency and yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon dioxide treatment, and in particular to a FeCoNiCuMo high entropy alloy nanocage electrocatalyst for carbon dioxide recycling, a preparation method thereof, and its reaction between CO2 and NO3 - Application in co-reduction. Background Art

[0002] Under the dual challenges of global climate change and energy crisis, it is particularly important to develop efficient and sustainable chemical conversion pathways. As the main greenhouse gas, excessive emissions of carbon dioxide (CO2) have exacerbated global warming, so there is an urgent need to reduce its concentration and achieve resource recovery through conversion technology. At the same time, nitrogen oxides (NO3 - ) is an important cause of eutrophication of water bodies. Developing effective methods to convert it into harmless or valuable compounds is of great environmental significance. As an important nitrogen fertilizer, the production process of urea traditionally relies on high-energy chemical processes, so finding a greener synthesis route has become a research hotspot.

[0003] In recent years, electrocatalytic technology has become a promising technology for the conversion of CO2 to NO3 due to its adjustability and environmental friendliness. - An effective way to co-reduction. Electrocatalytic reactions can be carried out at room temperature and pressure, significantly reducing dependence on traditional chemical processes. However, existing catalysts still have deficiencies in catalytic activity, selectivity and stability, and it is urgent to explore new catalytic materials to improve reaction efficiency.

[0004] As a new type of catalyst, high entropy alloy has multi-component and high entropy characteristics and exhibits excellent catalytic performance. In the field of electrocatalysis, the unique structure of high entropy alloy can effectively regulate the electronic and geometric properties of the catalyst, thereby improving its adsorption capacity and activation energy for reactants, and is expected to significantly improve the CO2 and NO3 - By utilizing the diversity and adjustability of high entropy alloys, precise optimization of catalyst performance can be achieved, thereby enhancing the selectivity and yield of the reaction.

[0005] CN110280255A discloses a FeCoNiCrCu nano high entropy alloy electrocatalyst and its application in electrocatalytic oxygen evolution. The method first dissolves a certain amount of urea and template agent sodium chloride in deionized water and stirs vigorously; then adds ferric nitrate nonahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, chromium nitrate nonahydrate and copper nitrate trihydrate, and stirs on a magnetic stirrer for 3 to 12 hours. The stirred solution is then placed in a refrigerator and frozen for 48 to 72 hours. After it is frozen solid, it is dehydrated in a vacuum dryer for 24 to 36 hours to finally obtain a precursor, which is then calcined at high temperature to obtain a product. The starting potential of the electrocatalyst for catalytic oxygen evolution reaction is 1.50 to 1.63 V, and the current density is 10 mA cm -2 The overpotential at 360 to 460 mV and the Tafel slope at 70 to 120 mV dec -1 , showing good catalytic activity. However, the synthesis process of the catalyst is relatively complicated and tedious.

[0006] Studies have shown that FeCoNiCuMo high entropy alloy thin films have been successfully synthesized. CN108728876A discloses an electroplating solution with deionized water as solvent, and prepares FeCoNiCuMo high entropy alloy thin films by electrochemical deposition. The preparation method is: using a graphite plate as an anode and a copper base as a cathode, dissolving each metal salt in trisodium citrate, triethanolamine, glycine, ethylene glycol, ascorbic acid and lithium perchlorate solution as an electrolyte, electroplating at a constant potential of 1.1 V for 3 minutes, and then rinsing with ethanol and deionized water and drying. Although the patent mentions its potential applications in the fields of heat-resistant, wear-resistant, and corrosion-resistant coatings, it does not explore its specific applications in the field of electrocatalysis, especially in the reaction between CO2 and NO3 - The effect of ion co-reduction in the preparation of urea is still unclear. This means that further research is needed to understand the performance and potential applications of the catalyst for the electrocatalytic synthesis of urea.

[0007] In electrocatalytic CO2 and NO3 - In the process of preparing urea, existing catalysts have some defects, such as single active site and CN bond matching, which leads to limited urea yield. - Catalysts for the preparation of urea still need continuous research and optimized design to overcome these challenges. Summary of the invention

[0008] The present invention is directed to CO2 and NO3 - The catalyst activity for electrocatalytic preparation of urea is not high, CO2 and NO3 - The matching of parallel reaction kinetics provides a balanced CO2 and NO3 -Preparation method of FeCoNiCuMo high entropy alloy nanocage electrocatalyst with reaction kinetics effect, the catalyst is used for CO2 and NO3 - Electrocatalytic preparation of urea can effectively adjust CO2 and NO3 - The reaction kinetics are well matched, and it has extremely high selectivity for CN coupling to synthesize urea, and it still has good stability under long-term operation.

[0009] To achieve the above object, the technical solution adopted by the present invention is:

[0010] A method for preparing a seed layer-induced FeCoNiCuMo high-entropy alloy nanocage electrocatalyst comprises the following steps:

[0011] Step 1, dispersing nickel salt, cobalt salt and iron salt in water, mixing and reacting, standing and aging, separating, purifying and drying to obtain FeCoNi nanocage catalyst, wherein the catalyst is dispersed in water to form a seed layer solution;

[0012] Step 2, adding copper salt and molybdate to the seed layer solution and ultrasonically mixing, adding pH regulator and reducing agent for ultrasonic treatment, placing the mixed solution in liquid nitrogen for cooling to initially nucleate, naturally thawing and standing to nucleate, and washing and freeze-drying to obtain the FeCoNiCuMo high entropy alloy nanocage electrocatalyst.

[0013] In the present invention, the seed layer induced template nucleation technology is used, and the FeCoNi nanocage is used as a template to help form a high entropy alloy catalyst with a specific morphology and structure. The presence of the template can not only guide the orderly arrangement of the components during the synthesis process, but also maintain the nanoscale structure of the catalyst, thereby improving the catalytic performance. The regulation of pH provides an acidic environment for the synthesis, which helps to adjust the reaction conditions and promote the uniform deposition and interaction of metal ions. At the same time, the crystal structure and surface characteristics of the catalyst can also be effectively controlled. In addition, the added reducing agent can provide a reducing environment during the synthesis process to promote the reduction reaction of the metal ions. By controlling the rate of the reduction reaction, the uniform nucleation and growth of the high entropy alloy can be achieved, thereby obtaining ideal catalytic performance.

[0014] The nickel salt includes one of nickel nitrate, nickel chloride and nickel sulfate;

[0015] The cobalt salt includes cobalt nitrate, cobalt chloride, and cobalt sulfate;

[0016] The iron salt is potassium ferrocyanide;

[0017] The copper salt includes one of copper nitrate, copper chloride or copper sulfate;

[0018] The molybdate includes one of sodium molybdate and potassium molybdate.

[0019] In step 1, the molar ratio of nickel salt, cobalt salt and iron salt is 0.8-1.2:0.8-1.2:0.8-1.2.

[0020] In step 1, the reaction temperature is room temperature, and the reaction time is 10-60 min; the static aging is standing at room temperature for 12-36 h.

[0021] Step 1 also includes a complexing agent, which includes one of sodium citrate and potassium citrate; the molar ratio of the complexing agent to the nickel salt is 1.5-3:1.

[0022] The pH regulator includes one or more of hydrofluoric acid, ammonium fluoride or acetic acid; the reducing agent includes one or more of sodium borohydride, oxalic acid or sulfite.

[0023] After the pH regulator is added, the pH of the solution is 4-6; the molar ratio of the reducing agent to the copper salt is 2-6:1.

[0024] In step 2, the first ultrasonic time is 10-30 min, the second ultrasonic time is 30-60 min; the liquid nitrogen freezing time is 5-30 min; and the standing time is 12-100 h.

[0025] Preferably, natural thawing is pre-thawing at room temperature for 5-15 min, and then completely thawing in an oven at 20-35°C for 20-60 min.

[0026] The molar ratio of the copper salt to the molybdate is 4:1-1:3. In order to obtain a high urea synthesis effect, the electronic and geometric properties of the FeCoNiCuMo high entropy alloy nanocage electrocatalyst obtained in the present invention can be precisely optimized by adjusting the metal ratio. By regulating the electronic structure and coordination environment of the high entropy alloy by the Mo content, new active sites can be created to enhance the versatility of the catalyst. These active sites can effectively promote the reaction of CO2 with NO3 - , improve the selectivity of the catalyst for CN bond formation, promote the CN coupling reaction, reduce the occurrence of side reactions, and increase the yield of urea. Preferably, the molar ratio of the copper salt to the molybdate is 4:1-1:1.

[0027] The molar mass ratio of the copper salt to the FeCoNi nanocage catalyst in the seed layer solution in step 2 is 4 mmol:50-200 mg.

[0028] In step 2, the cleaning is performed by washing with deionized water for 3-5 times and then washing with anhydrous ethanol for 1-3 times;

[0029] The present invention also provides a FeCoNiCuMo high entropy alloy nanocage electrocatalyst prepared by the preparation method. The obtained electrocatalyst presents a nanocage structure and has a rough surface.

[0030] The present invention also provides the FeCoNiCuMo high entropy alloy nano cage electrocatalyst in CO2 and NO3 - Application in electrocatalytic conversion of urea.

[0031] Preferably, in the application process, the FeCoNiCuMo high entropy alloy electrocatalyst is the working electrode, and the electrolyte is 0.5 M KNO3 + 0.5 M KHCO3 solution.

[0032] Further preferably, CO2 and NO3 are reduced at the cathode - In the reaction system, a three-electrode system is adopted, specifically, an Ag / AgCl electrode is used as a reference electrode, a carbon rod is used as a counter electrode, the FeCoNiCuMo high entropy alloy electrocatalyst is used as a working electrode, and KNO3 and KHCO3 are used as electrolytes.

[0033] Preferably, in CO2 and NO3 - In the process of electrocatalytic preparation of urea, the catalyst of the present invention can make the Faraday efficiency of the product urea be above 8%, preferably above 10%, further preferably above 15%, above 20%, and optimally can reach about 25%.

[0034] Preferably, when the Mo:Cu content is about 1:3, the urea output is 1116.25 µg / mg / h, with good output and good effect.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention prepares the entropy alloy nanocage structure by inducing the seed layer, thereby ensuring the stability and reactivity of the catalyst nanostructure. The FeCoNi nanocage seed layer not only provides a template to promote the orderly arrangement of the alloy components, but also maintains the uniformity of the nanoscale structure, so that the catalyst has a higher specific surface area and more abundant active sites, which significantly improves the catalytic efficiency.

[0037] (2) The present invention provides a FeCoNiCuMo high entropy alloy nanocage electrocatalyst that balances CO2 and NO3 by design - The reaction kinetics of CO2 and NO3 are effectively adjusted, achieving efficient synergy between the two and greatly improving the selectivity of urea synthesis. - The reaction kinetics are matched, thereby reducing the occurrence of side reactions and improving the efficiency of CN coupling and the yield of urea.

[0038] (3) The present invention adjusts the metal ratio of FeCoNiCuMo high entropy alloy, especially optimizes the Mo content, which helps to adjust the electronic structure and coordination environment of the high entropy alloy and create new active sites. This adjustment further enhances the catalyst's reaction to CO2 and NO3 - The synchronous conversion effect improves its versatility for urea synthesis and increases the selectivity and reaction efficiency of CN coupling. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is the X-ray diffraction pattern of the FeCoNiCuMo high entropy alloy catalyst prepared in Example 1.

[0040] Figure 2 Transmission electron microscope TEM and mapping image of the catalyst FeCoNiCuMo alloy prepared in Example 1.

[0041] Figure 3 The graph shows the urea production and Faraday efficiency of the FeCoNiCuMo high entropy alloy of Example 1 at different voltages.

[0042] Figure 4 This is a performance comparison chart of the catalyst in comparative example 1 and the catalyst in example 1 in synthesizing urea.

[0043] Figure 5 The performance comparison chart of the catalyst in Example 2 and the material in Example 1 for electrocatalytic synthesis of urea is shown. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0045] The raw materials used in the following specific embodiments are all purchased from the market.

[0046] Example 1

[0047] (1) Weigh 4 mmol of Ni(NO3)2·6H2O, 4 mmol of Co(NO3)2·6H2O and 9 mmol of sodium citrate and dissolve them in 200 mL of deionized water to form solution A. At the same time, dissolve 4 mmol of K4Fe(CN)6 in another 200 mL of deionized water to form solution B. Subsequently, solution B was added dropwise to solution A under magnetic stirring and stirred for 20 min. Thereafter, the mixed solution was aged at room temperature for 24 h. The subsequent separation and purification were carried out by centrifugation and washing with deionized water and ethanol; the precipitate was vacuum dried at 60 °C overnight, and the obtained sample was a FeCoNi nanocage seed catalyst;

[0048] (2) Take out 100 mg of FeCoNi nanocage seed catalyst and dissolve it in a beaker of 500 mL deionized water and stir it thoroughly. Add 4 mM Cu(NO3)2·3H2O and 1.33 mM Na2MoO4·3H2O to the above solution and treat it ultrasonically for 15 min. Then add 8 mM NH4F and 16 mM NaHB to the above solution, adjust the solution pH to about 7, and treat it ultrasonically for 40 min.

[0049] (3) Add sufficient amount of liquid nitrogen to the precursor solution obtained above and treat it for 15 min, then pre-thaw it at room temperature for 10 min, and completely thaw it in a 30°C oven for 30 min. Then let it stand at room temperature for 72 h and replace it with deionized water 6 times. Finally, place it at -110°C for freeze-drying for 24 h to obtain a black gel product, which is recorded as FeCoNiCuMo high-entropy alloy nanocage electrocatalyst;

[0050] The FeCoNiCuMo high entropy alloy nanocage electrocatalyst prepared in step (3) was observed for its microstructure and element distribution by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The XRD results are as follows: Figure 1 As shown in the TEM image Figure 2 As shown. Figure 1-Figure 2 It can be seen that the FeCoNiCuMo catalyst is a high-entropy alloy nanocage material with uniform element distribution.

[0051] Electrocatalytic CO2 and NO3 - Activity test: The FeCoNiCuMo catalyst obtained in step 3 was dispersed on carbon paper for electrocatalytic reduction reaction test to observe the catalytic activity of the catalyst. The results are as follows: Figure 3-Figure 5 As shown. It can be seen that when the Mo:Cu ratio of FeCoNiCuMo high entropy alloy nanocage catalyst is 3:1 and the voltage is -0.45 V, the urea production is 1116.25 µg / mg / h, indicating that the modified catalyst can electrocatalyze the conversion of CO2 and NO3 -The urea production activity is improved.

[0052] Comparative Example 1

[0053] The process of Example 1 is followed, except that step (1) is omitted and in step (2), the FeCoNi seed catalyst is not added but is replaced by 4 mmol of Ni(NO3)2·6H2O, 4 mmol of Co(NO3)2·6H2O and 4 mmol of Fe(NO3)3·9H2O to obtain a FeCoNiCuMo catalyst, which is recorded as FeCoNiCuMo-1.

[0054] Example 2

[0055] The process of Example 1 was followed, except that in step (2), 1.33 mM sodium molybdate was replaced with 1 mM, 4 mM, 12 mM and 16 mM to obtain FeCoNiCuMo nanocage electrocatalysts with different Mo contents, corresponding to Cu:Mo ratios of 4:1, 1:1, 1:3 and 1:4, respectively, denoted as FeCoNiCuMo-I, FeCoNiCuMo-II, FeCoNiCuMo-III, and FeCoNiCuMo-IV.

[0056] Example 3

[0057] The process of Example 1 was followed, except that in step (2), 100 mg of the FeCoNi nanocage seed catalyst was replaced with 50 mg and 200 mg, and FeCoNiCuMo nanocage electrocatalysts were obtained accordingly.

[0058] Application example: Catalysts for electrocatalytic reduction of CO2 and NO3 - Urea production

[0059] (1) A three-electrode system was used, with the catalyst prepared in the examples and comparative examples as the working electrode, the counter electrode as a carbon rod, the reference electrode as a saturated Ag / AgCl electrode, and the electrolyte as 0.5 M potassium nitrate + 0.5 M potassium bicarbonate;

[0060] (2) Activation: Using Shanghai Chenhua CHI 760E electrochemical workstation, carbon dioxide was introduced into the electrolyte for 30 min before testing. Cyclic voltammetry was used, with the test interval at 0-1 V vs. RHE and a scan rate of 10 mV s -1 After 50 cycles, the electrode reaches a stable state.

[0061] First, the FeCoNiCuMo nanocage catalyst in Example 1 was tested for urea production and its Faraday efficiency under different voltage conditions, with the voltage range being between -0.2 V and -0.6 V, to observe the effect of voltage on its performance. Figure 3As shown, the urea production performance of the FeCoNiCuMo nanocage electrocatalysis at -0.45 V in Example 1 is better than that at other potentials.

[0062] The activity of the FeCoNiCuMo nanocage material in Example 1 and the catalyst FeCoNiCuMo-1 without FeCoNi seed template in Comparative Example 1 were tested to examine the urea yield and Faraday efficiency under the optimal voltage of -0.45 V. Figure 4 As shown in Table 1, the catalyst with the nanocage structure in Example 1 exhibits more excellent performance, indicating that the structure of the catalyst prepared by seed layer induction helps to better expose the active sites and has higher catalytic activity.

[0063] The activity of the FeCoNiCuMo nanocage material in Example 1 and the different Mo contents in Example 2 were tested to examine the urea production under the optimal voltage of -0.45 V. Figure 5 As shown in Table 1, the catalyst of the FeCoNiCuMo nanocage material constructed in Example 1 exhibits more excellent performance, indicating that appropriate regulation of Mo is helpful for the reaction of CO2 with NO3 - co-reduction.

[0064] Table 1 Catalytic performance data of the catalysts of the examples and comparative examples at a voltage of -0.45 V

[0065] Serial number Cu:Mo molar ratio Cu: Seed catalyst (mmol:mg) Urea production (µg / mg / h) Faraday efficiency (%) Example 1 3:1 4:100 1116.25 25.2 Example 2 4:1 4:100 715.12 11.4 Example 2 1:1 4:100 865.20 13.1 Example 2 1:3 4:100 632.51 9.7 Example 2 1:4 4:100 356.27 4.8 Comparative Example 1 3:1 4:0 456.27 6.2 Example 3 3:1 4:50 705.25 10.4 Example 3 3:1 4:200 954.2 18.9

[0066] Examples 1 and 3 show the performance data of nanocage materials prepared with different amounts of seed catalyst. It can be seen that the effect is better with an appropriate amount of seed catalyst. Too little or too much will affect the dispersion of copper and cobalt, and thus affect the catalytic performance of the catalyst. However, the overall effect is very good within the range of Cu:seed catalyst of 4:50-200 mmol:mg.

Claims

1. A method for preparing a seed layer-induced FeCoNiCuMo high-entropy alloy nanocage electrocatalyst, characterized in that: Includes steps: Step 1, dispersing nickel salt, cobalt salt and iron salt in water, mixing and reacting, and then standing, aging, separating, purifying and drying to obtain FeCoNi nanocage catalyst, wherein the catalyst is dispersed in water to form a seed layer solution; Step 1 also includes a complexing agent, which includes one of sodium citrate and potassium citrate; Step 2, adding copper salt and molybdate to the seed layer solution and ultrasonically mixing, adding pH regulator and reducing agent for ultrasonic treatment, placing the mixed solution in liquid nitrogen for cooling to initially nucleate, naturally thawing and standing to nucleate, and washing and freeze-drying to obtain the FeCoNiCuMo high entropy alloy nanocage electrocatalyst.

2. The method for preparing the seed layer induced FeCoNiCuMo high entropy alloy nanocage electrocatalyst according to claim 1, characterized in that: The nickel salt includes one of nickel nitrate, nickel chloride and nickel sulfate; The cobalt salt includes one of cobalt nitrate, cobalt chloride and cobalt sulfate; The iron salt is potassium ferrocyanide; The copper salt includes one of copper nitrate, copper chloride or copper sulfate; The molybdate includes one of sodium molybdate and potassium molybdate.

3. The method for preparing the seed layer induced FeCoNiCuMo high entropy alloy nanocage electrocatalyst according to claim 1, characterized in that: In step 1, the molar ratio of nickel salt, cobalt salt and iron salt is 0.8-1.2:0.8-1.2:0.8-1.2; In step 1, the reaction temperature is room temperature, the reaction time is 10-60 min, and the static aging is 12-36 h at room temperature; The molar ratio of the complexing agent to the nickel salt is 1.5-3:

1.

4. The method for preparing the seed layer induced FeCoNiCuMo high entropy alloy nanocage electrocatalyst according to claim 1, characterized in that: The pH regulator includes one or more of hydrofluoric acid, ammonium fluoride or acetic acid; the reducing agent includes one or more of sodium borohydride, oxalic acid or sulfite.

5. The method for preparing the seed layer induced FeCoNiCuMo high entropy alloy nanocage electrocatalyst according to claim 1, characterized in that: After the pH regulator is added, the pH of the solution is 4-6; the molar ratio of the reducing agent to the copper salt is 2-6:

1.

6. The method for preparing the seed layer induced FeCoNiCuMo high entropy alloy nanocage electrocatalyst according to claim 1, characterized in that: In step 2, the first ultrasonic time is 10-30 min, the second ultrasonic time is 30-60 min; the liquid nitrogen freezing time is 5-30 min; and the standing time is 12-100 h.

7. The method for preparing the seed layer induced FeCoNiCuMo high entropy alloy nanocage electrocatalyst according to claim 1, characterized in that: The molar ratio of the copper salt to the molybdate is 4:1-1:

3.

8. The method for preparing the seed layer induced FeCoNiCuMo high entropy alloy nanocage electrocatalyst according to claim 1, characterized in that: The molar mass ratio of the copper salt to the FeCoNi nanocage catalyst in the seed layer solution in step 2 is 4 mmol:50-200 mg.

9. A FeCoNiCuMo high entropy alloy nanocage electrocatalyst prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the FeCoNiCuMo high entropy alloy nanocage electrocatalyst according to claim 9 in the electrocatalytic conversion of urea from O2 and NO3⁻.

Citation Information

Patent Citations

  • Preparation method of FeCoNiCuMo high-entropy alloy film

    CN108728876A

  • Nano-high-entropy alloy electrocatalyst and preparation method thereof

    CN110280255A

  • Alloy nanocage catalyst, and preparation method and application thereof

    CN110444774A

  • High-entropy alloy and preparation method thereof, membrane electrode assembly and fuel cell

    CN116574957A